Penilaian Kualitas Website Sistem Informasi Magang Menggunakan Metode Webqual (Studi Kasus: PT Wiyata Indo Global) - Fasya Medytha; Salsabila Putri Apriani (CV. Shofanah Media Berkah, 2025)
Websites have become an essential medium for institutions to deliver information quickly and efficiently. PT Wiyata Indo Global utilizes its Internship Information System website to provide internship related information and manage online registration; however, several issues remain, including suboptimal navigation, inconsistent interface design, and unstable access speed. This study applies the WebQual 4.0 method to assess the website’s quality based on the perceptions of 52 student respondents. The findings reveal that the Information Quality dimension obtained the highest score (4.12), indicating that the internship details and registration procedures are presented clearly and are easy for users to understand. The Satisfaction (4.11) and Service Interaction (4.07) dimensions also received strong evaluations. Meanwhile, System Reliability (3.93) requires improvements concerning system stability, and Usability (3.52) becomes the key area needing enhancement. Overall, the website is categorized as good; however, improvements in navigation, system performance, and interface consistency are recommended to further enhance user experience.